Duhovna razsežnost v zdravstveni negi slepih z vidika logoteoretskega razumevanja človeka - Slabe, Damjan (Obzornik zdravstvene nege, 1998)
The article shows the importance of the spiritual dimension of the person in the holistic approach of the nurse to the blind patient in the process of nursing care. The author places the spiritual dimensioninto the framework of logotheoretical understanding of the human being. In the article logotherapy is presented as a theoretical and practical starting point trying to help the man in need; the blind patients to become aware and to realize concerete possibilities to fulfill the meaning of the moment, the meaning of his/her concrete life situation. It helps to search the meaning of suffering and tragedy of the life in darkness and emphasizes the responsibility of an individual in decision making. The article is supported by results of a qualitative study and in the conclusion the author also aduces concrete suggestions for practical work.
Keywords: komunikacija; logoterapija; slepota; zdravstvena nega